Расчет: eUwVtf - 1

F  = 
 
 k* q1* q2
/ r^2
F =  
 k* q1* q2
/ r^2
 = 
 
 k* q1* q2
/ r^2
 = F = 
 
 1
/ r^2
 =  
 F
/ k/ q1/ q2
 = 
r = saknis( 
 k* q1* q2
/ F
)
 = 
r = saknis( 
 9* ×10^9* (-19)* (-19)
/ 14
)
 = 
r = saknis( 
 9* ×10^9* (- 1.9* 10)* (-19)
/ 14
)
 = 
r = saknis( 
 9* ×10^9* 1.9* (0.52631578947368-10)* (-19)
/ 14
)
 = 
r = saknis( 
 9* ×10^9* 1.9* (0.52631578947368-10)* (- 1.9* 10)
/ 14
)
 = 
r = saknis( 
 9* ×10^9* 1.9* (0.52631578947368-10)* 1.9* (0.52631578947368-10)
/ 14
)
 = 
r = saknis( 2.3207142857143* ×10^9* (0.52631578947368-10)* (0.52631578947368-10)) = 
r = saknis( 2.3207142857143* ×10^9* (0.52631578947368-10)^2) = 
r = saknis( 2.0828571428571* 10^2* ×10^9) = 
r = saknis( 2.0828571* 10^2* ×10^9) = 
r = ( 1.44321* 10* ×10^4* saknis(×10)) = 
r =  1.44321* 10* ×10^4* saknis(×10) =